(untitled) (Texas Journal of Agriculture and Biological Sciences, 2023)
Fast-food consumption has become a phenomenon of significant proportions, witnessing a remarkable surge in prevalence over the past few decades. The ubiquity of fast-food chains, characterized by their accessibility and affordability, has contributed to a significant shift in dietary patterns worldwide. The study assessed fast and processed foods consumption and health. It was revealed that the surge in fastfood consumption is not merely a dietary choice but has broader implications for public health. It has been associated with an increased risk of non-communicable diseases, including obesity, cardiovascular issues, and metabolic disorders, thereby posing substantial challenges to global health. As societies increasingly adopt fast-food as a staple in their diets, understanding its global prevalence becomes crucial for formulating effective public health strategies. The study concluded that the idler our stomachs are, the longer they will last. The more we tax our stomach, the soonest it will wear out. Take time and prepare your own food. Do not kill yourselves by running to the store and buying processed fast foods to eat. We need to change our focus and become more respectful of the human body as the true house of the living God. There is no house on earth more holy than this wonderful magnificent structure created by the Lord of the Worlds. We ought to clean it up